35.0k views
3 votes
In order to solve for the variable in the equation 2 (x + 3) + 5 x = 3 (2 x minus 1), Jaleesa begins by applying the distributive property, then combines like terms. Which equation is the result of these steps? 7 x + 6 = 6 x minus 3 2 x + 6 + 5 x = 6 x minus 3 2 x + 3 + 5 x = 6 x minus 1 7 x + 3 = 6 x minus 1

2 Answers

5 votes

Answer:

The answer is A

Explanation:

I did the quiz and got it right. Also, its the only one that makes sense!!

;) Duhh....

User Borstenhorst
by
5.0k points
3 votes

Answer:

7x + 6 = 6x - 3

Explanation:

2(x+3) + 5x = 3(2x-1)

Distribute

2x + 6 + 5x = 6x - 3

Combine like terms

7x + 6 = 6x - 3

User Marcus Kaseder
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.